2015
DOI: 10.1016/j.blre.2014.12.003
|View full text |Cite
|
Sign up to set email alerts
|

How we will treat chronic myeloid leukemia in 2016

Abstract: Imatinib will become generic in 2016; assuming that its price will decrease precipitously, we expect that the economic forces will change our current practice habits. We reviewed the literature on the current recommendations to treat chronic myeloid leukemia and highlight how we plan to deal with these changes. Specifically, we propose to better characterize patients according to prognostic scores, to allow more attention to those at high risk for disease progression, e.g., three-month guidelines and BCR/ABL1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…Thus, there is the necessity of searching for new targets and personalized therapies (16,37,38). In addition, our data indicate that BGB324 is active in BCR-ABL TKIresistant CML cells and mouse models, including T315I-mutated and ponatinibresistant systemic mouse models and primary cells.…”
Section: Discussionmentioning
confidence: 78%
“…Thus, there is the necessity of searching for new targets and personalized therapies (16,37,38). In addition, our data indicate that BGB324 is active in BCR-ABL TKIresistant CML cells and mouse models, including T315I-mutated and ponatinibresistant systemic mouse models and primary cells.…”
Section: Discussionmentioning
confidence: 78%
“…The risk of death was associated with the advanced phase at the diagnosis, discontinuation of imatinib therapy, and the failure or insufficient response during the treatment with imatinib. Indeed, for patients who fail frontline therapy with imatinib, second-line options must be started including second-and third-generation TKIs [25][26][27], all of which are unavailable in our country. For patients in advanced phase at the diagnosis, Thota et al [28] found that even though imatinib can enable cytogenetic remission, survival remains lower than in patients in chronic phase at diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Comparatively, there are fewer NHW ALLs in the 2002–2011 period, which can be caused by changes in both incidence and diagnosis. There are multiple treatment strategies for leukemia 14 , 15 , including induction chemotherapy, consolidation therapy (or intensification therapy), preventive therapy, maintenance treatments with chemotherapeutic drugs, and others. For most cases, radiation is not the mainline treatment, as has been observed in this analysis.…”
Section: Discussionmentioning
confidence: 99%